IL12 immune therapy clinical trial review: Novel strategies for avoiding CRS-associated cytokines - Jia, Zhiliang; Ragoonanan, Dristhi; Mahadeo, Kris Michael; Gill, Jonathan; Gorlick, Richard; Shpal, Elizabeth; Li, Shulin (Frontiers in Immunology, 2022)
Interleukin 12 (IL-12) is a naturally occurring cytokine that plays a key role in inducing antitumor immune responses, including induction of antitumor immune memory. Currently, no IL-12-based therapeutic products have been approved for clinical application because of its toxicities. On the basis of this review of clinical trials using primarily wild-type IL-12 and different delivery methods, we conclude that the safe utilization of IL-12 is highly dependent on the tumor-specific localization of IL-12 post administration. In this regard, we have developed a cell membrane-anchored and tumor-targeted IL-12-T (attIL12-T) cell product for avoiding toxicity from both IL-12- and T cells-induced cytokine release syndrome in peripheral tissues. A phase I trial using this product which seeks to avoid systemic toxicity and boost antitumor efficacy is on the horizon. Of note, this product also boosts the impact of CAR-T or TCR-T cell efficacy against solid tumors, providing an alternative approach to utilize CAR-T to overcome tumor resistance.